Hemophagocytic syndrome and COVID-19. (2020) - Lima, Ricardo; Filho, Célio Cortinhas; Ferreira Filho, Carlos Martins; Vaisman, Mauricio; Cossenza, Alexandre; Rebello, Caroline Pinto; Leite, Carolina de Andrade; de Oliveira Tavares, Danilo; Ramalho, Julia Falconiere
Abstract: The case of a woman hospitalized due to COVID-19 is presented. The patient developed a severe macrophage activation syndrome diagnosed by bone marrow biopsy, which did not respond to immunoglobulin therapy.